CRC handbook pf organic photochemistry and photobiology (CRC Press, 1994)
The book is divided according to the chemical structure of the subtraste undergoing irradiation. It deals with hydrocarbons, oxygen-containing compounds, sulfur-containing compounds, nitrogen-containing compounds, and halogenated compounds